# Math

posted by .

Is the derivative of (squarerootof x)/(3x+1) : 3x+1-3squarerootofx/(2squarerootofx)(3x+1)^2

• Math -

y = √x/(3x+1)

y' = (1/2√x (3x+1) - √x (3)) / (3x+1)^2
= (3x+1) - 2√x√x(3)) / 2√x (3x+1)^2
= (1-3x) / 2√x (3x+1)^2

Looks like you forgot a factor of √x:

y = u/v
y' = (u'v - uv')/v^2

• Math -

also ,my own typing was sloppy.

y' = (1/(2√x) (3x+1) - √x (3)) / (3x+1)^2

Looks like you forgot to put the numerator over a common denominator of 2√x

## Similar Questions

the derivative of 2x^e is zero right or no?
2. ### calc

derivative of (x^3/6)+(1/2x)? i got (x^2/2)-(1/2x^2) is that correct?
3. ### Calculus--> bobpursley

How do you get m=0? from taking the second derivative?
4. ### Derivatives- Math

Can someone explain how to find the derivative of : 1. y= 5^ãx / x And the second derivative of: y= xe^10x For this question I got up to the first derivative and got this y = e^10x + 10xe^10x but I can't seem to get the correct …
5. ### Calculus

Find the dervatives: 1. f(x)=(3x+1)e^x^2 2. y = e^(sin x) ln(x) 3. f(x)=(x^(2)+x)^23 4. f(x)=sin(2x)/cosx 5. square root of x/(3x+1) 6. f(x)=sin^4(3x=1)-sin(3x+1) 7. x+y=cos(xy) The answers I got: 1. 6x^(2)e^(x^2)+2xe^(x^2)+3e^(x^2) …
6. ### math

Let f be a real value function and x Î Df then 0 lim ( ) ( ) h f x h f x ® h + - when it exists is called A) The derivative of f at a B) The derivative of f at h C) The derivative of f at x D) The derivative of f at x = h
7. ### math

Find the derivative of y=3x-2(4^x) Here is my attempt: Derivative of 3x is 3 Derivative of 2 is 0 derivative of 4^x is 4^x(ln(4)) Answer: 12^x(ln(4)) Is this correct?
8. ### Math (Derivative)

Computer the derivative of f(x)=x-(1/x) for x>0 using the definition of the derivative.
9. ### Math (Derivative)

Compute derivative using the definition of the derivative. f(x)=1+1/x^2 1+ 1/(x+h)^2 - (1+ 1/(x^2)) ------ divide by h and multiply by reciprocal 1/h(x+h)^2 - 1/hx^2 Next I expanded it and got this messy huge number and multiply the …
10. ### Math Derivative

Find derivative of f(x)=g(h(x)) Would the derivative be something like: g'(h(x))*h'(x) ?

More Similar Questions